ACCELERATED FRACTAL ENCODING VIA DOMAIN CLASSIFICATION - Ziyad T. Najim (Science Journal of University of Zakho)
The story of fractal image compression is that the image to be compressed is partitioned into many blocks (range pool). Domain pool is created from range pool. Then, each range block is compared with all domain blocks, searching for the best match. This comparison process is highly time-consuming. Many ideas were proposed trying to reduce search time. Here in this paper, a fractal image encoding algorithm based on domain pool classification and domain pool reduction is proposed to speed up the searching process. It works on classifying domain blocks—according to some criteria—into many classes. In this way, range blocks are compared only with the domain blocks that belong to the same class as the range blocks. Experiments showed a considerable reduction in encoding time when compared with the standard Fisher's fractal image compression algorithm while maintaining image quality.